State-owned banks in the transition : origins, evolution, and policy responses - Sherif, Khaled; Borish, Michael S.; Gross, Alexandra (Washington, DC : World Bank, 2003)
The study examines the history and evolution of state banks in the transition economies of Europe and Central Asia
Includes bibliographical references (p. 119-122).
osc 9/09/2021
Loans
Keywords: Banks and banking; Banks and banking; Privatization